2017
DOI: 10.1002/ird.2098
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Root Zone Soil Water Content Estimation in Agricultural Lands Using Bayesian-Based Artificial Neural Networks and High- Resolution Visual, NIR, and Thermal Imagery

Abstract: Soil moisture is an important parameter in irrigation scheduling and application. Knowledge of root zone volumetric water content can support decisions for more efficient irrigation management by enabling estimation of required water application rates at appropriate temporal and spatial scales. The study presented here proposes a data mining approach that combines known field conditions with remote sensing observations to provide probabilistic estimates of root zone soil moisture at three different depths in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 56 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…While numerous studies have been conducted with thermal inertia, the triangle approach and microwave to estimate SM from satellite and manned airborne remote sensing [11,36,63,64], only few studies have been conducted with UAS observations [4,17,19]. For instance, Sobrino et al (2012) used NDVI and T s with a polynomial formulation to predict SM and this approach can estimate SM with RMSDs of 0.05 m 3 •m −3 from observations from a manned airborne system [64].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous studies have been conducted with thermal inertia, the triangle approach and microwave to estimate SM from satellite and manned airborne remote sensing [11,36,63,64], only few studies have been conducted with UAS observations [4,17,19]. For instance, Sobrino et al (2012) used NDVI and T s with a polynomial formulation to predict SM and this approach can estimate SM with RMSDs of 0.05 m 3 •m −3 from observations from a manned airborne system [64].…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…However, studies on the quantification of SM from UAS imagery are relatively limited. Hassan-Esfahani et al (2015, 2017) conducted the first UAS studies to estimate SM from optical and thermal images by using an artificial neural network [4,17]. Results indicate that SM can be retrieved with root mean square deviations (RMSDs) equal to 0.05 m 3 •m −3 .…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3 shows a root zone soil volumetric water content (%) map (pixel-wise at 0.15m resolution) for the first AggieAir flight [7].…”
Section: Resultsmentioning
confidence: 99%
“…The review of current literature indicates that soil water content (SWC) and grain yield relationship has not been thoroughly studied from a time and depth perspective, and least of all at the field scale. Hassan-Esfahani, et al [11] presented one of the few studies on the estimation of SWC at the root zone, using high resolution remote sensing data, and demonstrated the potential of vegetation indices to estimate SWC, but did not link SWC to crop yield. A recent review paper have identified the need for a combined soil-based and crop-based approach to better estimate crop water needs [12].…”
Section: Introductionmentioning
confidence: 99%